Project work is a promise for the school in a country that dreams - Segura, Dino
Project work has recently been proposed again as an alternative to transform the school and perhaps make it more efficient. This article argues that achieving this possibility will allow an opportunity to leave the school organization focused on the curriculum. While the curriculum is structured around old statements and information, project work refers to live, current events; While the first is the result of external determinations to school processes, project work is the product of the interests and meanings of the protagonists; while the curriculum has to do with information, project work is committed to knowledge.